ESTABLISHING COOPERATION BETWEEN UNIVERSITY AND INDUSTRY IN KAZAKHSTAN: ANALYSIS OF LEGAL AND POLICY DOCUMENTS - Altynbassov Бақыт Өмірханұлы; Bayanbayeva Әйгерім Рақымғалиқызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
This article examines the legal frameworks and challenges in promoting cooperation between universities and industry in Kazakhstan, emphasizing the initiatives and obstacles in this collaborative endeavour. The focus is on the "Concept of the Development of Higher Education and Science in the Republic of Kazakhstan for 2023-2029," proposed by the Kazakhstani government, which aims to transform regional universities into innovative hubs closely linked with industry. Although this concept is progressive, the article explains that it requires legislative changes and amendments to be effectively implemented. The Ministry of Science and Higher Education’s efforts to propose regulatory changes to improve collaboration between universities and industry and the government’s preference for offering incentives to industries are also discussed. However, the article emphasizes the slow speed of legislative processes and a lack of inter-ministerial cooperation as significant challenges that hamper the achievement of these initiatives. The analysis focuses on the only legal provision in place, the Code of the Republic of Kazakhstan on Subsoil Use, which mandates companies to invest in personnel training and research. The article highlights the limited functionality of this Code and the absence of a comprehensive legal framework that mandates industry-university collaboration. Furthermore, the article explores the state’s centralized governance and its influence on collaboration between universities and industry in Kazakhstan. The aim is to give a complete comprehension of the current and future possibilities of cooperation, which is necessary for Kazakhstan’s socio-economic development and innovation landscape.